2007
DOI: 10.1194/jlr.m700299-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and phospholipase function of peroxiredoxin 6: identification of the catalytic triad and its role in phospholipid substrate binding

Abstract: Peroxiredoxin 6 (Prdx6) is a bifunctional protein with glutathione peroxidase and phospholipase A 2 (PLA 2 ) activities, and it alone among mammalian peroxiredoxins can hydrolyze phospholipids. After identifying a potential catalytic triad (S32, H26, D140) from the crystal structure, site-specific mutations were used to evaluate the role of these residues in protein structure and function. The S32A mutation increased Prdx6 a-helical content, whereas secondary structure was unchanged by mutation to H26A and D14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(164 citation statements)
references
References 34 publications
13
148
1
Order By: Relevance
“…We observed that phospholipase activity-dead S32A Prx6 mutant considerably lost its antiapoptotic activity. As this mutant shows a marked change of secondary structure and protein folding, 30 the role of phospholipase activity of Prx6 in TRAIL-induced cell death is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that phospholipase activity-dead S32A Prx6 mutant considerably lost its antiapoptotic activity. As this mutant shows a marked change of secondary structure and protein folding, 30 the role of phospholipase activity of Prx6 in TRAIL-induced cell death is not clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the C47S Prdx6 mutant partially rescued (ϳ50%) both the agonist-induced PLA 2 activity and ROS generation (Table 4). On the other hand, there was no significant rescue of either PLA 2 activity or ROS generation in endothelial cells transfected with constructs that express S32A, H26A, or D140A mutant Prdx6; these 3 amino acids constitute the Prdx6 PLA 2 catalytic triad, and each is necessary for PLA 2 activity but not for H 2 O 2 peroxidase activity (21,22). These results for "rescue" show that the PLA 2 activity of Prdx6 is required for Ang II-mediated activation of NOX2 in mouse PMVEC.…”
Section: Ros Production With Ang II Treatment Of Lung Endothelium In mentioning
confidence: 99%
“…An Inhibitor of Acute Lung Injury • Fisher AB acid mutagenesis based on the crystal structure of the protein (17) revealed that surface-located amino acids located around the S32 are important for binding of the protein to the phospholipid substrate (58). We have proposed that the insertion of the sn-2 fatty acid of phospholipids into a narrow crypt positions it for either reduction (peroxidase activity) or hydrolysis (PLA 2 activity) (Fig.…”
Section: Peroxiredoxinsmentioning
confidence: 99%
“…[Reproduced with permission from Manevich et al (58).] An Inhibitor of Acute Lung Injury • Fisher AB acid mutagenesis based on the crystal structure of the protein (17) revealed that surface-located amino acids located around the S32 are important for binding of the protein to the phospholipid substrate (58).…”
Section: Peroxiredoxinsmentioning
confidence: 99%
See 1 more Smart Citation